On-Chip ESD Protection for Integrated Circuits An IC Design Perspective - Wang, Albert Z. H. (The International Series in Engineering and Computer Science,, 2002)
This comprehensive and insightful book discusses ESD protection circuit design problems from an IC designer's perspective. On-Chip ESD Protection for Integrated Circuits: An IC Design Perspective provides both fundamental and advanced materials needed by a circuit designer for designing ESD protection circuits, including: Testing models and standards adopted by U.S. Department of Defense, EIA/JEDEC, ESD Association, Automotive Electronics Council, International Electrotechnical Commission, etc. ESD failure analysis, protection devices, and protection of sub-circuits Whole-chip ESD protection and ESD-to-circuit interactions Advanced low-parasitic compact ESD protection structures for RF and mixed-signal IC's Mixed-mode ESD simulation-design methodologies for design prediction ESD-to-circuit interactions, and more! Many real world ESD protection circuit design examples are provided. The book can be used as a reference book for working IC designers and as a textbook for students in the IC design field.